Biotransformação do pesticida metil paration por fungos isolados da ascídia Didemnum ligulum - Rodrigues, Gisele Nunes (Universidade Federal de São Carlos, 2013)
Pesticides are potentially toxic compounds to humans and other living beings, which are indispensable for pests removal in agriculture worldwide. The result of their overuse is the inevitable contamination of aquatic and terrestrial ecosystems. The need for degradation of these compounds has been subject of several studies. The enzymatic biodegradation of synthetic pesticides by microorganisms is an important strategy for removing these pollutants from the environment. Marine fungi are an excellent source of highly oxygenated bioactive compounds with huge potential to biotransform xenobiotics such as pesticides. Thus, the objective of this project was to study the biotransformation of the organophosphate pesticide methyl parathion using fungi of marine origin isolated from the ascidian Didemnum ligulum. Initially, 17 fungi strains have undergone screening on agar culture medium containing different pesticide concentrations (120 mg/L, 240 mg/L and 360 mg/L), and the three strains that showed the greatest growth diameter of the colony, were subjected to culture in a liquid medium to quantify the possible degradation of the methyl parathion. For these strains, the eficiency of degradation was monitored by high performance liquid chromatography (HPLC). Methyl parathion was almost completely degraded in 20 days, but there was no significant difference between the reactions with the fungi strains and the abiotic control. The microorganisms, however, showed ability to metabolize p-nitrophenol, the main degradation product of methyl parathion. In conclusion, these three marine fungi, identified as two strains of Penicillium citrinum and one strain of Fusarium proliferatum, have proven to be important sources to study xenobiotic biotransformation.
Keywords: Microbiologia; Biodegradação; Pesticidas; Fungos marinhos; Organofosforados; Xenobióticos; Organophosphorous; Xenobiotics; Marine fungi; Biodegradation; CIENCIAS BIOLOGICAS::ECOLOGIA